Peroxidase from infected fruit of Solanum sp. grown in Nsukka - KO, Omeje; SOO, Eze; Chilaka, FC (Bangladesh Journal of Scientific and Industrial Research, 2019)
In this study, we characterized the activity of peroxidase a quality control enzyme from the infected fruit of Solanum sp. Peroxidase was purified to homogeneity by ammonium sulfate precipitation, dialysis, ion exchange chromatography and size exclusion chromatography. The molecular weight of the native enzyme was 63000 da. The enzyme was shown to have two iso-enzymes with distinct optimum pH of 4.5 and 7.0 and optimum temperature of 40 and 70⁰C. The purified enzyme had broad substrate specificity with o-dianisidine being the ideal substrate. Na+, Ca2+, Mg2+, Mn2+, Cu2+, Al3+ were shown to be activators of the enzyme, while the peroxidase activity was severely inhibited by Co2+. Bangladesh J. Sci. Ind. Res.54(2), 131-138, 2019